Evaluation of C-reactive protein and myxovirus resistance protein A to guide the rational use of antibiotics among acute febrile adult patients in Northwest Ethiopia. (December 2020) - Akelew, Yibeltal; Derbew, Agegnehu; Lemma, Mulualem; Negash, Markos; Bewket, Gezahegn; Belay, Gizeaddis; Pollmann, Julia; Adriaensen, Wim; Adane, Aynishet; Mohammed, Rezika; van Griensven, Johan; Cnops, Lieselotte
Highlights: The cause of acute fever in low resource settings is often unknown due to lack of diagnostics. This leads to the overconsumption of antibiotics. Rapid, low-cost diagnostic tools can easily be integrated into clinical practice. We evaluated 2 biomarkers to differentiate bacterial from non-bacterial infections in Ethiopia. Abstract: Objectives: In low-resource settings, treatment is often given empirically without knowledge of the aetiology due to a lack of diagnostics. In the search for reliable rapid tests to guide treatment work-up, this study was performed to determine whether two biomarkers could differentiate bacterial from non-bacterial infections in acute febrile patients. Methods: Adults with acute fever were recruited at a referral hospital in Ethiopia. The QuikRead Go test was used to quantify C-reactive protein (qCRP) and the FebriDx test was used for combined qualitative detection of the bacterial CRP marker with myxovirus resistance protein A (MxA), a viral biomarker. Results: Of the 200 patients included in this study, most presented with 2–3 days of fever, headache, and joint pain. Antibiotics were prescribed for 83.5% and antimalarials for 36.5%, while a bacterial infection was only confirmed in 5% and malaria in 11%. The median qCRP level for confirmed bacterial infections was 128 mg/l. The FebriDx and QuikRead Go test had an overall agreement of 72.0%. Conclusions: An over-prescription of antibiotics for febrile patients was observed, even for those with low CRP levels and without a confirmed bacterial infection. The added value of the FebriDx was limited, while the combined use of rapid tests for qCRP and malaria should be considered for the management of acute febrile illness and antibiotic stewardship.